AUTHENTIC AND NON-AUTHENTIC MATERIALS IN TEACHING LISTENING SKILLS (Modern education and development, 2024)
In language education, teaching listening skills has become increasingly important as listening comprehension is fundamental for effective communication. Among the various methods for teaching listening, the use of authentic and non-authentic materials plays a significant role in shaping learners' listening abilities. Authentic materials, such as real-life conversations, news reports, and podcasts, provide learners with exposure to natural language, while non-authentic materials, such as scripted dialogues or textbook exercises, are designed with pedagogical goals in mind. This article explores the key differences between authentic and non-authentic materials, their advantages and disadvantages, and their impact on developing listening skills. It also highlights the importance of selecting appropriate materials for learners at different proficiency levels.